Library construction for ancient genomics: Single strand or double strand?. (June 2014) - Bennett, E. Andrew; Massilani, Diyendo; Lizzo, Giulia; Daligault, Julien; Geigl, Eva-Maria; Grange, Thierry
A novel method of library construction that takes advantage of a single-stranded DNA ligase has been recently described and used to generate high-resolution genomes from ancient DNA samples. While this method is effective and appears to recover a greater fraction of endogenous ancient material, there has been no direct comparison of results from different library construction methods on a diversity of ancient DNA samples. In addition, the single-stranded method is limited by high cost and lengthy preparation time and is restricted to the Illumina sequencing platform. Here we present in-depth comparisons of the different available library construction methods for DNA purified from 16 ancient and modern faunal and human remains, covering a range of different taphonomic and climatic conditions. We further present a DNA purification method for ancient samples that permits the concentration of a large volume of dissolved extract with minimal manipulation and methodological improvements to the single-stranded method to render it more economical and versatile, in particular to expand its use to both the Illumina and the Ion Torrent sequencing platforms. We show that the single-stranded library construction method improves the relative recovery of endogenous to exogenous DNA for most, but not all, of our ancient extracts.